1969
DOI: 10.1017/s0022377800004347
|View full text |Cite
|
Sign up to set email alerts
|

More uniform perturbation theory of the Vlasov equation

Abstract: The Vlasov—Poisson equations are reformulated by applying an arbitrary transformation to the velocity variable in such a way that perturbation theory of the transformed equations does not exhibit the customary secularity in time (or space) in second or higher order. The lowest order approximation of the new formulation is discussed and compared with conventional results. The source of the non-uniformity appears to be the divergence of Particle trajectories as calculated by perturbation methods, from the exact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1969
1969
2010
2010

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…where subscript ' 1 ' denotes a perturbed quantity. It is important to assume small perturbations, since secular (divergent) terms appear at second order in a straightforward expansion of the Vlasov-Poisson equations (Lewak 1969). The equations to be solved now are >…”
Section: Assumptionsmentioning
confidence: 99%
“…where subscript ' 1 ' denotes a perturbed quantity. It is important to assume small perturbations, since secular (divergent) terms appear at second order in a straightforward expansion of the Vlasov-Poisson equations (Lewak 1969). The equations to be solved now are >…”
Section: Assumptionsmentioning
confidence: 99%
“…where £ is the new independent velocity variable (Lewak 1969). With the transformation (2.1), (1.1) becomes…”
Section: Perturbationmentioning
confidence: 99%
“…In a previous paper [Lewak (1969), see also Pfirsch (1966) for related treatment], it was shown that the Vlasov equation in the Semi-Lagrangian (S.L.) formulation, may be written in a form resembling the fluid equations.…”
mentioning
confidence: 99%